Comparison of pregnancy outcomes in amniocentesis recipients with normal and abnormal maternal serum analytes: Pregnancy outcomes and maternal serum analytes - Shoarishoar, Seyedeh Shahed; Milani, Forozan; Adineh, Samira; Sorouri, Zahra Rafiei; Maryam Attari, Seyedeh (Cellular and Molecular Biology, 2024)
Considering the relatively high frequency of genetic disorders associated with negative pregnancy outcomes, in this research, adverse pregnancy outcomes in amniocentesis patients were compared between two groups with normal and abnormal maternal serum analytes. This retrospective cohort study was conducted on singleton pregnant women who underwent amniocentesis and had fetuses with normal chromosomes at the perinatology clinic in Rasht. Eligible patients were divided into two groups of 307 people with normal and abnormal maternal serum analytes based on laboratory screening results. Adverse pregnancy outcomes were compared between the two groups. In a total of 614 pregnant women, adverse pregnancy outcomes were observed in 24% of the abnormal analyte group and 15% of cases in the normal analyte group. The association between adverse pregnancy outcomes and both normal and abnormal analytes was found to be statistically significant (p<0.05). the most common adverse pregnancy outcome was hypertensive disorders, which was more prevalent in the abnormal analyte group (10.7%). The presence of abnormal levels of free beta-human chorionic gonadotropin (free β-hCG) and inhibin-A factors were found to be associated with adverse pregnancy outcomes. Specifically, for each unit increase in inhibin-A level, the likelihood of experiencing an adverse pregnancy outcome was reported to be 1.83 times higher (OR=1.83, P=0.028). Similarly, the presence of abnormal free β-hCG values was associated with a 3.12 times higher chance of adverse pregnancy outcomes (OR=3.115, P=0.03). The utilization of serum analytes for first and second-trimester screening can be beneficial in the prediction of adverse pregnancy outcomes, particularly hypertensive disorders during pregnancy.